Non-canonical DNA structures in the human ribosomal DNA - Smirnov, Evgeny; Molínová, Pavla; Chmúrčiaková, Nikola; Vacík, Tomáš; Cmarko, Dušan (Histochemistry and cell biology, 2023)
Non-canonical structures (NCS) refer to the various forms of DNA that differ from the B-conformation described by Watson and Crick. It has been found that these structures are usual components of the genome, actively participating in its essential functions. The present review is focused on the nine kinds of NCS appearing or likely to appear in human ribosomal DNA (rDNA): supercoiling structures, R-loops, G-quadruplexes, i-motifs, DNA triplexes, cruciform structures, DNA bubbles, and A and Z DNA conformations. We discuss the conditions of their generation, including their sequence specificity, distribution within the locus, dynamics, and beneficial and detrimental role in the cell.
Keywords: konformace nukleové kyseliny; Non-canonical DNA; G-kvadruplexy; lidé; ribozomální DNA; rDNA; G-Quadruplexes; DNA, Ribosomal; DNA quadruplexes; Nucleic Acid Conformation; R-loops; Humans